Analisis Kerentanan Tsunami di Bandar Lampung Menuju Mitigasi Era Industri 4.0: (Studi Kasus Tsunami Selat Sunda 2018) - Susanti Sundari (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
This research aims to analyze the vulnerability of the city of Bandar Lampung to tsunamis with a case study of the 2018 Sunda Strait Tsunami and at the same time provide an overview of past conditions and mitigation concepts to the community that are in accordance with the development of Industry 4.0 today and in the future, using qualitative methods descriptive with case studies. This method is used to reveal the problems behind the visible data can provide greater understanding the phenomena that occur. The research result is known that the potential for Tsunami vulnerability is due to the geographical location and the existence of Mount Krakatau which is a threat to tsunamis caused by earthquakes, volcanic eruptions, coastal and underwater landslides. Apart from that, public ignorance about tsunami in disaster preparedness is needing serious attention. The development of appropriate Industrial 4.0-based tsunami detection and early warning tools that can monitor in real time requires regulatory support as a sustainable management strategy. Efforts to increase people's knowledge and ability to face the threat of disaster can be done through education and outreach by creating disaster mitigation programs that are visionary, easy to implement and right on target using digital media.